2022
DOI: 10.1097/dss.0000000000003550
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Stimulation for Aesthetic Body Shaping: A Comprehensive and Critical Review

Abstract: BACKGROUND Aesthetic muscle stimulation (AMS) using high-intensity electromagnetic field (HIFEM) targets skeletal muscle neurons, causing muscle hypertrophy and loss of adipose tissue, thereby cultivating a sculpted physique. Many studies have evaluated AMS for noninvasive body contouring; however, the efficacy, safety, and long-term data remain unclear. OBJECTIVE To critically evaluate the current literature on the use of electromagnetic muscle stimulation for body contouring and provide a consensus on patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…7 More recently, toned and sculpted arms have increasingly been of interest in aesthetics, however, there are few studies evaluating the efficacy of muscle stimulation for toning and strengthening of the upper arms. 6,13,14 HIFEM was previously demonstrated to be of benefit in toning arms of 18 HIFEM-treated patients, with a mean 15% increase in biceps brachii muscle thickness 1 month following treatment and sustained at 6-month follow-up according to ultrasound measurements. This study also demonstrated a 13% and 15% decrease in adipose tissue overlying biceps brachii muscle at 1 and 6-month follow-up, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7 More recently, toned and sculpted arms have increasingly been of interest in aesthetics, however, there are few studies evaluating the efficacy of muscle stimulation for toning and strengthening of the upper arms. 6,13,14 HIFEM was previously demonstrated to be of benefit in toning arms of 18 HIFEM-treated patients, with a mean 15% increase in biceps brachii muscle thickness 1 month following treatment and sustained at 6-month follow-up according to ultrasound measurements. This study also demonstrated a 13% and 15% decrease in adipose tissue overlying biceps brachii muscle at 1 and 6-month follow-up, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The design of this bioelectrical muscle stimulator system has revolutionized EMS technology, in that it can maximize targeted muscle contraction while minimizing energy dispersion to surrounding epidermis and dermis, thus significantly reducing the risk of burn and discomfort that have been reported to occur with conventional EMS-based devices. 6,[9][10][11][12] Furthermore, this system can target multiple muscle groups (i.e., biceps and triceps) in the same 30-min treatment period, compared to HIFEM-based systems that are only able to target one muscle group at a time thereby maximizing treatment efficiency. 7,12,16,17 The data presented herein also demonstrates efficacy for patients regardless of assigned gender and age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations